Getting to know the Awá Tikal Nationality in Ecuador, cultural and linguistic aspects - Obando Arroyo, José Miguel (Tierra Infinita, 2024)
The Awá is one of the fourteen indigenous nationalities that currently live in Ecuadorian territory. Their myths, legends, language and more cultural manifestations, as well as their lifestyle, strongly connect these people to the jungle, the place where they live, from where they get their food and the place that they protect. This document study attempted to determine the themes and ranges of previous research about the cultural features and language of the Awá Nationality in Ecuador. The reviewed works corresponded to publications between 2001 up to 2023. The accounts evidenced that the information published describe, analyze and discuss the situation of the Awá Nationality in Ecuador in aspects like their origin, the region where they live, how they are organized and their culture, including the myth of their origin legends and the language which is in endangered.
Keywords: Awá; Ecuador; Awapit